Making Space in the Academy for the Curriculum of Belonging: Exploration of Indigenous Self, Coloniality and Relationships to Land - Scott, Michelle Elizabeth (Journal of the Canadian Association for Curriculum Studies, 2020)
What does it mean to reconcile our relationships with the Land, the assimilative and violent policies of the settler colonial project that is now Canada? How can we begin to understand our own responsibilities as we relate to this Land and all our relations? How do we untangle our familial curriculum of dislocation, as we unravel the stories of the wounds and bloodlines that make up our physical, social and spiritual DNA? Taking up these questions alongside Simpson’s (2014) wholistic definition of theory as “generated and regenerated continually through embodied practice and with each family, community and generation of people” (p. 7), I began my journey from the fractures of my familial wounds, the wounds of my Mi’kmaq ancestors and their ignored relationships to the Land in Ktaqmkuk (Newfoundland). Through journal entries, poetry and photographs, I documented my journey to familial sites in Ontario and Newfoundland with my teenage sons in the summer of 2019 as my own emerging curriculum of belonging. As educators, it is incumbent upon us to allow similar epistemic spaces for all learners to interrogate their own complex histories as they relate to the Land, coloniality and to the thousands-year-old relationships Indigenous peoples of North America have had with the Land. We must make spaces for them to invite the embodied, familial, personal stories to take form so that they can begin to enter their own curriculum of belonging (and responsibility) with this Land, wherever they are.